Phonological potentials and the lower vocal tract - Moisik, Scott Reid (2021)
This paper outlines a theoretical approach to speech sound systems based on the notion of phonological potentials: physical ‘pressures’ or biases that give rise to discrete structure and the tendencies associated with this structure that arise from the physical nature of speech sound systems. We apply this approach to a poorly understood area of phonology – phenomena of the lower vocal tract (LVT) – through a schematic that encapsulates the complex interactions among the vocal tract structures responsible for producing LVT sounds. With the framework, we provide an account of a range of LVT phenomena from several languages, illustrating how tonal, phonatory, and vowel qualities interact. Finally, we consider how the idea of phonological potentials extends across various physical domains and might exhibit patterns of alignment across these domains, thereby serving to guide the formation of patterns found in speech sound systems.